ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERSERO PABRIK GULA CAMMAING DI KAB. BONE - Rusdi, H Muh; Alam, Muh Samsul (Jurnal Ekonomi Balance, 2013)
In this research method used descriptive research and regression analysis. Descriptive method is in the form of collecting data taken from various literatures and direct observation to the object of research, while the method of analysis is done by using the calculation of regression, correlation, determination and for hypothesis testing using t test. From all analyzes that have been done in this research can be concluded that if the work environment made a top priority for PT Persero Camming Sugar Factory it will improve the employee performance that ultimately this can provide benefits to PT Persero Camming Sugar Factory. Keywords: Analysis, Work Environment, Employee Performance, PT Persero Camming Sugar Factory